We're alone : essays - Danticat, Edwidge, 1969- (Graywolf Press, 2024)
"Tracing a loose arc from Edwidge Danticat's childhood to the COVID-19 pandemic and recent events in Haiti, the essays gathered in We're Alone include personal narrative, reportage, and tributes to mentors and heroes such as Toni Morrison, Paule Marshall, Gabriel García Márquez, and James Baldwin that explore several abiding themes: environmental catastrophe, the traumas of colonialism, motherhood, and the complexities of resilience. From hurricanes to political violence, from her days as a new student at a Brooklyn elementary school knowing little English to her account of a shooting hoax at a Miami mall, Danticat has an extraordinary ability to move from the personal to the global and back again. Throughout, literature and art prove to be her reliable companions and guides in both tragedies and triumphs. Danticat is an irresistible presence on the page: full of heart, outrage, humor, clear thinking, and moral questioning, while reminding us of the possibilities of community. And so "we're alone" is both a fearsome admission and an intimate invitation-we're alone now, we can talk. We're Alone is a book that asks us to think through some of the world's intractable problems while deepening our understanding of one of the most significant novelists at work today"--